2014
DOI: 10.1109/jqe.2014.2310196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Maxwell–Schrödinger and Maxwell–Newton Hybrid Simulations for Multi-Well Electrostatic Potential

Abstract: A novel hybrid approach to the dynamics of electron interacting with time-dependent electromagnetic fields, namely, the Maxwell-Schrödinger approach, has been employed to study a system of electron confined in single-and multi-well electrostatic potentials subjected to pulsed laser fields. A comparison of the results of simulation to those obtained by the conventional Maxwell-Newton approach has been made by calculating the time response of the current density and the time-evolution of the electric field at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Very recently, we have examined a reliability of the conventional Maxwell-Newton hybrid scheme for an electron confined in one-dimensional potential wells. A comparison of computational results with those obtained by the corresponding Maxwell-Schrödinger scheme [6] has revealed that both results agree very well for a harmonic single-well potential while disagree qualitatively for a triple-well potential where a harmonic potential is artificially supplemented by two small humps allowing bifurcation of the electron wave packet. Although this study clearly demonstrates necessity of use of the Maxwell-Schrödinger scheme over the conventional Maxwell-Newton one particularly when quantum-mechanical tunnelling takes place, an effect of anharmoicity in a singlewell confining potential on computational results has not been fully explored.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Very recently, we have examined a reliability of the conventional Maxwell-Newton hybrid scheme for an electron confined in one-dimensional potential wells. A comparison of computational results with those obtained by the corresponding Maxwell-Schrödinger scheme [6] has revealed that both results agree very well for a harmonic single-well potential while disagree qualitatively for a triple-well potential where a harmonic potential is artificially supplemented by two small humps allowing bifurcation of the electron wave packet. Although this study clearly demonstrates necessity of use of the Maxwell-Schrödinger scheme over the conventional Maxwell-Newton one particularly when quantum-mechanical tunnelling takes place, an effect of anharmoicity in a singlewell confining potential on computational results has not been fully explored.…”
Section: Introductionmentioning
confidence: 81%
“…where J represents the polarization current density which is defined by the time derivative of the polarization vector P. Since the electromagnetic fields have only E y and H z components in the present study, they can be updated by the following recursion relations based on the Maxwell FDTD method [5,6,10]:…”
Section: Maxwell-schrödinger Hybrid Schemementioning
confidence: 99%
See 3 more Smart Citations